KEPUTUSAN PEMBELIAN SAYURAN DI PASAR JATINEGARA SELAMA PANDEMI COVID-19 DENGAN PENERAPAN THEORY OF PLANNED BEHAVIOR - Harahap, Yerho David Hasudungan; Aprilia, Anisa; Maulidah, Silvana (Universitas Sebelas Maret, 2023)
Large-Scale Social Restrictions (PSBB) is one of the Indonesian government's policies in dealing with the COVID-19 pandemi. In the midst of the implementation of the policy, consumers are still buying food, one of which is vegetables, directly to traditional markets. This study uses a quantitative approach through descriptive statistical analysis and SEM-PLS analysis using WarpPLS 7.0. This study aims to examine the effect of the Theory of Planned Behavior variables, namely attitudes, subjective norms, and perceptions of behavioral control on consumer purchase intentions and vegetable purchasing decisions at Jatinegara Market during the COVID-19 pandemi. The types of data in this study are primary data and secondary data using 45 respondents who were determined using the judgment sampling method. The results showed that the variables of attitude, subjective norm, and perceived behavioral control had an effect on consumers' purchase intentions. The biggest indicator contribution to the attitude variable is convenience in making purchases. Meanwhile, the biggest indicator contribution to the subjective norm variable is support from close friends. And on the behavioral control perception variable, the biggest indicator is the ability to make purchases. Traders and market managers need to maintain and improve the application of health protocols in the Jatinegara Market area, especially during the COVID-19 pandemi, so that consumers' purchase intentions remain high to buy vegetables.